Motyw starości w wybranych utworach Franciszka Karpińskiego - Szymczak, Ewelina (Starość i młodość w literaturze i kulturze, 2016)
The present article focuses on the aspect of old age in Franciszek Karpiński’s works. The mainobject of the article is to analyse an Enlightenment reflection on the category of anthropological timein selected poems and a sentimental diary of Karpiński. Rich, however not innovative, chronosophicalreflection of the writer, complies with the Enlightenment critique model of old age understood as timeof physical constraints and lack of attraction resulted from changes influenced on a human body.